Shorea henryana - JENIS MERANTINON REKALSITRANT - Usep Soetisna; Dody Priadi (BERITA BIOLOGI, 2005)
Shorea henryana - a member species of Dipterocarpaceae known as white meranti. Ecologically distributed on lowland Dipterocarp forest and flourishing in coastal areas. A fairly large tree up to 40 m tall with bole up to 115 cm diameter. Seeds were dispatched from Thailand and showing 72% germination and initial moisture content of 20.3%. First lot of seeds were dried to moisture content 12.5%, 9.4% and 6.1% respectively. Germination of seeds dried to 6.1% m.c. was still relatively high (68%). Contrary to the desiccation resistance, however, the dried seeds seemed not to withstand relatively low temperature for Shorea species, i.e. 14-16 C. Further study will be needed as to investigate a proper storage treatment for this important woody species.